Med žlindro in svitlo mavro - Mandić, Lucija (Slavistična revija, 2019)
By using a comparative analysis of the reception of two national poems, Prešeren's The Baptism on the Savica and Mácha's May, we can observe in which ways the processes of canonization of these works were similar and in which ways they differed during the nineteenth-century period of national revivals. By researching private correspondence, literary critiques, and literary reception, we can see how the perception of these works has changed from 1836, when they were first published, up until they became recognized as canonical works in their respective national literatures.
Keywords: Czech literatura; Czech poets; Czech Romanticism; Czech Romanticists; češka književnost; češka romantika; češki pesniki; češki romantiki; Mácha, Karel Hynek; nacionalna pesnitev; national poem; Prešeren, France; Slovene literature; Slovene poets; Slovene Romanticism; Slovene Romanticists; slovenska književnost; slovenska romantika; slovenski pesniki; slovenski romantiki